Morphological spectrum and epidemiological profile of ovarian tumours in black West African women at Lagos state university teaching hospital, Ikeja, Nigeria - Sanni, Daniel A.; Soyemi, Sunday S.; Popoola, Abiodun O.; Rabiu, Kabiru A. (International Journal of Research in Medical Sciences, 2020)
Background: This study was done to evaluate the histological types, frequency and age distribution of ovarian tumours in Lagos State University Teaching Hospital (LASUTH), Ikeja, Lagos State. This study also aims to classify ovarian tumours in this centre according to the World Health Organisation (WHO). Methods: A retrospective, descriptive hospital study of all ovarian specimens that were sent to the department of pathology and forensic medicine, LASUTH between 1st January, 2011 and 31st December, 2019 was done. Relevant data composed of the age distributions and histopathological types were extracted from the departmental information system and filed documents. The data was analysed using the IBM-SPSS version 25.0. Results: There were 198 cases of ovarian tumours. The mean age at diagnosis of ovarian tumours was 34.6±15.3 years. Unilateral ovarian tumour was observed in 91.9%% of cases while bilateral disease was seen in 8.1%. Primary ovarian tumours constitute 97.0% of all diagnosed tumours of the ovary. Germ cell tumour was the most frequently diagnosed ovarian tumour; and teratoma was the most common, representing 91.2% of germ cell tumours and 47.0% of all ovarian tumours. Primary ovarian cancer peaked at the 6th decade of life and metastatic ovarian cancer was infrequently seen. Serous carcinoma is the most commonly diagnosed ovarian cancer. Conclusions: Ovarian tumour presents most frequently at the 4th decade of life, and germ cell tumour is the most common.